Finite element wear prediction using adaptive meshing at the modular taper interface of hip implants. (January 2018) - Bitter, Thom; Khan, Imran; Marriott, Tim; Lovelady, Elaine; Verdonschot, Nico; Janssen, Dennis
Abstract: The use of modular components in total hip arthroplasty introduced an additional interface with the potential for fretting and corrosion to occur. Fretting and corrosion at this interface have been reported as a potential cause of early failure of the implant system. Using finite element (FE) analyses the mechanics at the taper junction can be studied. However, most FE studies are based on a single load condition and do not take geometry changes over time into account. Therefore, in this study an FE routine was developed, in which adaptations to the implant geometry are made to account for material removal during the fretting process. Material removal was simulated based on Archard's Law, incorporating contact pressure, micromotions and a wear factor which used input from in vitro fretting tests. A wear factor of 2.7*10 −5 mm 3 /N mm was used to match the FE predicted volumetric wear to the measured experimental volumetric wear of 0.79 mm 3 after 10 million cycles. The maximum experimental wear depth found was 30.5 ± 17 µm, while the FE predicted a maximum wear depth of 27 µm. The adaptive meshing method has delivered results that are more similar to the experimental test data in comparison to the results from modelling a single cycle without adaptive meshing.